2017
DOI: 10.15406/mojpb.2017.05.00177
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Pharmacokinetic of Highly Specific Novel Pan-Mtor Inhibitors against Solid Tumors

Abstract: Mechanistic/mammalian target of rapamycin (mTOR) a serine/threonine kinase belonging to PI3K/Akt/mTOR pathway is involved in different cellular functions cell survival, metabolism, growth, proliferation, apoptosis and autophagy. PanmTOR inhibitors are targeted towards mTOR dysregulation, inhibiting the kinase domain of both mTORC1 and mTORC2. The present study analyzes the binding modes and molecular interactions of highly specific mTOR inhibitors, AZD8055 and its sister compoundAZD2014using computational appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The structure-based pharmacophore and MD analysis of the mTOR-PP242 crystal structure revealed that the inhibitor targets key residues Asp2195, Gly2238 and Val2240 via hydrogen bonds entailing essential pharmacophoric features including HBD and HBA ( Figure 1 B and Figure S2A ). It has been elucidated in previous studies that hydrogen bonds with Asp2195 and Val2240 are indispensable for mTOR inhibitory activity [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In the current study, Hit1 was observed to retain the hydrogen bonding interaction with Asp2195 ( Table 3 , Figure 4 A), while Hit4 interaction with both residues was preserved even after 30 ns of production simulation run ( Table 3 , Figure 4 D).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure-based pharmacophore and MD analysis of the mTOR-PP242 crystal structure revealed that the inhibitor targets key residues Asp2195, Gly2238 and Val2240 via hydrogen bonds entailing essential pharmacophoric features including HBD and HBA ( Figure 1 B and Figure S2A ). It has been elucidated in previous studies that hydrogen bonds with Asp2195 and Val2240 are indispensable for mTOR inhibitory activity [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In the current study, Hit1 was observed to retain the hydrogen bonding interaction with Asp2195 ( Table 3 , Figure 4 A), while Hit4 interaction with both residues was preserved even after 30 ns of production simulation run ( Table 3 , Figure 4 D).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Hit1 was observed to retain the hydrogen bonding interaction with Asp2195 ( Table 3 , Figure 4 A), while Hit4 interaction with both residues was preserved even after 30 ns of production simulation run ( Table 3 , Figure 4 D). Additionally, our hits formed hydrogen bonds with catalytic hydrophilic residue Asp2357 of the mTOR ATP-binding site which offers a level of specificity for our hits towards mTOR than PI3K ( Figure 4 ) [ 51 , 52 , 53 , 54 , 55 ]. The compound Hit2 also formed additional hydrogen bonds with residues Lys2187 and Thr2245 ( Figure 4 B) and interactions with these residues were also reported in previously published studies [ 22 , 51 , 52 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation